The Influence of Adhesion Temperature to the Shear Strength of Width Glued Wooden Elements. (2015) - Obucina, Murco; Gondzic, Enil; Manso, Edib
Abstract: This paper examined the effect of temperature of pressing on the strength of width glued elements during the process of production of solid wood panels. It has been used the polyvinylacetate D3 adhesive and solid beech wood ( Fagus silvatica ). Time of pressing has been determinate separately for each level of temperature of bonding, which amounted to (30 o, 40°, 50°, 60°, 70 o C). For each level has been formed 20 samples in order to determinate the value of the shear strength of bonded joint. The results were processed using the Student's t -test. This research showed that with increasing the temperature and pressing time increases the shear strength of the bonded joint, but non-linear.